Increased Anxiety, Akathisia, and Suicidal Thoughts in Patients with Mood Disorder on Aripiprazole and Lamotrigine - Pondé, Milena Pereira; Freire, Antonio Carlos Cruz (Case Reports in Psychiatry, 2015)
Introduction. Akathisia affects around 18% of patients with bipolar disorder treated with aripiprazole and may worsen when aripiprazole is combined with lamotrigine and antidepressants. Case. This paper reports on two clinical cases involving patients with a diagnosis of mood disorder who developed severe akathisia, anxiety, and suicidal ideation while using a combination of aripiprazole, antidepressants, and lamotrigine. Discussion. We recommend that patients with a mood disorder taking multiple drugs should begin aripiprazole therapy with low doses and be monitored for the development of akathisia, increased anxiety, or suicidal thoughts. The appearance of these limiting side effects requires discontinuation of the drug.